Mixed Stand vs Monoculture : a Simulation Study Assessing Growth and Profitability of Norway spruce and Birch in Mixtures and Pure Stands - Dosumu, Babatunde (SLU/Southern Swedish Forest Research Centre, 2022)
Picea abies L. Karst (N. spruce) monocultures dominate the forest landscape of southern Sweden due to their suitability for the prevalent site conditions, well established silviculture, and profitability. However, disturbances such as windthrow, bark beetle damage, and Heterobasidion root rot pose a risk to N.spruce stands' stability. Consequently, recent studies recommend increased tree species diversity in production forests as a form of risk reduction in addition to securing multiple ecosystem services. The natural regeneration potential of birch in southern Sweden makes it a suitable species for establishing mixed stands with N.spruce. However, much research is still required to effectively manage these mixtures and develop silvicultural guidelines. Inventory data after the first PCT from well-replicated mixed species experiment with naturally regenerated birch and planted N.spruce on scarified soil were used as starting values to project stand development in the Heureka decision support system (StandWise). The experiments were established on highly fertile sites in southern Sweden namely: Hörja, Tagel, and Tönnersjöheden. Two thinning treatments, one aimed at maintaining species proportion (_mix) and another removing the smallest trees of either species (_TFB), were applied to the mixed stands, which had different initial species proportions B2S1 (66% Birch, 33% N.spruce) and B1S2 (33% Birch, 66% N.spruce). In contrast, thinning for pure stands was according to common silviculture for N.spruce and birch monoculture (_mono). Based on the thinning treatments, birch proportion (% basal area), growth (MAImax), and profitability (LEV) of N.spruce-birch stands were assessed in comparison to N.spruce and birch monoculture at final felling.